Evaluation of the Friction of Self-Ligating and Conventional Bracket Systems - Tecco, Simona; Iorio, Donato Di; Nucera, Riccardo; Bisceglie, Beatrice Di; Cordasco, Giancarlo; Festa, Felice (European Journal of Dentistry, 2011)
Objectives: This in vitro study evaluated the friction (F) generated by aligned stainless steel (SS) conventional brackets, self-ligating Damon MX© brackets (SDS Ormco, Glendora, California, USA), Time3© brackets (American Orthodontics, Sheboygan, Wisconsin, USA), Vision LP© brackets (American Orthodontics), and low-friction Slide© ligatures (Leone, Firenze, Italy) coupled with various SS, nickel-titanium (NiTi), and beta-titanium (TMA) archwires. Methods: All brackets had a 0.022-inch slot, and the orthodontic archwires were 0.014-inch, 0.016-inch, 0.014×0.025-inch, 0.018×0.025-inch, and 0.019×0.025-inch NiTi; 0.017×0.025-inch TMA; and 0.019×0.025-inch SS. Each bracket-archwire combination was tested 10 times. In the test, 10 brackets of the same group were mounted in alignment on a metal bar. The archwires moved through all the 10 brackets at a crosshead speed of 0.5 mm/min (each run lasted approximately 5 min). The differences among 5 groups of brackets were analyzed through the Kruskal-Wallis test, and a Mann-Whitney test was calculated as post hoc analysis. The P value was set at 0.05. Results: Coupled with 0.014-inch NiTi and 0.016-inch NiTi, Victory Series© brackets generated the greatest F, while Damon MX© and Vision LP© brackets generated the lowest (P<.05); no significant differences were observed between Time3© brackets and Slide© ligatures. Coupled with all the rectangular archwires, Victory Series© brackets, Slide© ligatures, and Vision LP© self-ligating brackets generated significantly lower F than did Time3© and Damon MX© self-ligating brackets (P<.05). Conclusions: These findings suggest that self-ligating brackets are a family of brackets that, in vitro, can generate different levels of F when coupled with thin or thick, rectangular, or round archwires. Clinical conclusions based on our results are not possible due to the limitations of the experimental conditions. (Eur J Dent 2011;5:310-317)
Keywords: Friction; Orthodontic brackets; Ligation